Studi Kasus Penjadwalan Proyek: Frame Acid Skid dengan Gant Chart dan Critical Path Method - Pujo Leksonowati, Nur Fitria; Pamungkas, Nurman; Stefani, Windy; Purba, Adi Syahputra; Manurung, Meilani Mandhalena; Batubara, Ninda Hardina; Gunawan, Leo Van (Politeknik Negeri Indramayu, 2024)
This study examines the scheduling of the Frame Acid Skid project at the Lombok Steam Power Plant (PLTU) using Gantt Chart and Critical Path Method (CPM). The primary objective is to identify the causes of delays and propose optimization measures for the project duration. Data collected indicates a significant difference between the planned duration (24 days) and the actual project completion time (47 days). The main delays occurred in the welding and painting phases, each requiring an additional 13 days. Contributing factors include the addition of a welding process for materials not covered in the initial contract and specification mismatches in the painting phase. Analysis with Gantt Chart and CPM reveals that enhanced communication, more detailed initial planning, and strict monitoring of project specifications are crucial to minimize the impact of delays on cost and time. The results of this study provide a strong basis for decision-making in similar future projects.